In defense of Japan : from the market to the military in space policy - Pekkanen, Saadia M. (Stanford University Press, 2010)
"In Defense of Japan provides the first complete, up-to-date, English-language account of the history, politics, and policy of Japan's strategic space development. The dual-use nature of space technologies, meaning that they cut across both market and military applications, has had two important consequences for Japan. First, Japan has developed space technologies for the market in its civilian space program that have yet to be commercially competitive. Second, faced with rising geopolitical uncertainties and in the interest of their own economics, the makers of such technologies have been critical players in the shift from the market to the military in Japan's space capabilities and policy. This book shows how the sum total of market-to-military moves across space launch vehicles, satellites and spacecraft, and emerging related technologies, already mark Japan as an advanced military space power"--Provided by publisher.